Pre-existing mental health disorders and fear of COVID-19 pandemic: Data from a phone survey in community-dwelling older adults recruited in the NutBrain study - Perdixi, Elena; Bernini, Sara; Conti, Silvia; Jesuthasan, Nithiya; Cotta Ramusino, Matteo; Costa, Alfredo; Prinelli, Federica (Frontiers in Psychiatry, 2022)
COVID-19 has caused a parallel epidemic of fear, anxiety, depression, stress, and frustration, particularly among the most fragile and vulnerable individuals, such as older people and those with previous mental health disorders. The present study aims to investigate the association between pre-existing mental health disorders, particularly depressive symptoms and Mild Cognitive Impairment (MCI), and the fear of COVID-19 and to explore which cognitive domains were involved in coping with fear in older people. In April 2020, we conducted a phone-interview questionnaire on community-dwelling older adults living in Lombardy Region (Italy) who participated in the NutBrain study. At baseline, socio-demographic characteristics along with lifestyles, and medical history were recorded. Participants underwent a neuropsychological battery exploring the global cognitive function and specific cognitive domains, to detect cases of MCI. The Center for Epidemiologic Studies Depression scale (CES-D) was used for screening depressive symptoms. During the phone survey, respondents were assessed using a structured questionnaire querying about fear of the COVID-19 pandemic. We performed multivariate logistic regression models to study the association between MCI and depressive symptomatology and fear. We also explored which cognitive domains were associated with fear. Odds Ratios (OR) with Confidence Intervals (95%CI) were estimated adjusting for potential confounders. Out of the 351 respondents (mean age 73.5±6.1 years, 59.8% women, 49.1% high education), at baseline, 22.9% had MCI and 18.8% had depressive symptoms. In the multivariate analyses gender, age, and body mass index were significantly associated with the fear score. Considering different domains of fear, MCI was associated with fear of being infected themselves (OR 2.55, 95%CI 1.39-4.70) while depressive symptoms were associated with fear of contagion for family members (OR 2.38,95%CI 1.25-4.52). Impaired executive cognitive function was positively associated with the highest tertile of the fear score (OR 3.28,95%CI 1.37-7.74) and with fear of contagion for themselves (OR 3.63,95%CI 1.71-7.69). Older adults experienced different fear reactions, particularly when suffering from neurocognitive disorders and depressive symptoms; executive dysfunction was associated with increased fear. These results highlighted the need to pay attention to the psychological effects of the outbreak of COVID-19 to target intervention, especially among vulnerable subgroups of individuals.